The Effect of Adding Sufentanil to 0.5% Hyperbaric Bupivacaine on Duration of Brachial Plexus Blockade in Chronic Opium Abusers: a Randomized Clinical Trial - Azimaraghi, Omid (Anesth Pain Med, 2015)
BACKGROUND: Anesthesia induction in patients with current substance abuse can be a challenge for anesthesiologists. OBJECTIVES: This study aimed to evaluate the effect of adding Sufentanil to Bupivacaine on duration of brachial plexus nerve block. PATIENTS AND METHODS: One hundred and twenty patients with (Groups C and D) and without (Groups A and B) a history of opium abuse (60 in each group) scheduled for elective upper extremity procedures were randomly assigned to either receive 30 mL bupivacaine alone (Groups A and C) or in combination with additional 10 µg sufentanil (Groups B and D). An ultrasound-guided technique was applied to perform upper extremity brachial plexus blockade. The onset and duration of sensory and motor blocks were recorded and compared between the four groups. RESULTS: The duration of sensory and motor block were significantly less in Group C (537.0 ± 40.1 minutes, 479.0 ± 34.8 minutes) and the longest duration of sensory and motor block was observed in group B (705.0 ± 43.8 minutes, 640.0 ± 32.5 minutes). The duration of sensory and motor block in Group B (705.0 ± 43.8 minutes, 640.0 ± 32.5 minutes) was longer and statistically higher than group A (619.5 ± 48.0 minutes, 573.2 ± 31.5 minutes), the same trend was observed in group D (598.6 ± 53.2 minutes, 569.3 ± 39.9 minutes) over group C (537.0 ± 40.1 minutes, 479.0 ± 34.8 minutes) (P < 0.001, one-way ANOVA). CONCLUSIONS: The length of sensory and motor blockade is shorter in chronic opioid abusers. Adding 10 µg sufentanil to hyperbaric bupivacaine in opium abusers lengthened the sensory and motor block duration.